Drivers for low-acuity pediatric emergency department visits in two tertiary hospitals in Switzerland: a cross-sectional, questionnaire-based study - Manon Jaboyedoff; Carl Starvaggi; Joan-Carles Suris; Claudia E. Kuehni; Mario Gehri; Kristina Keitel (BMC Health Services Research, 2024)
Abstract Purpose Low-acuity pediatric emergency department (PED) visits are frequent in high-income countries and have a negative impact on patient care at the individual and health system levels. Knowing what drives low-acuity PED visits is crucial to inform adaptations in health care delivery. We aimed to identify factors associated with low-acuity PED visits in Switzerland, including socioeconomic status, demographic features, and medical resources of families. Methods We conducted a prospective, questionnaire-based study in the PEDs of two Swiss tertiary care hospitals, Bern and Lausanne. We invited all consecutive children and their caregiver attending the PED during data collection times representative of the overall PED consultation structure (e.g. day/night, weekdays/weekends) to complete a questionnaire on demographic features, socioeconomic status, and medical resources. We collected medical and administrative data about the visit and defined low-acuity visits as those meeting all of the following criteria: (1) triage category 4 or 5 on the Australasian Triage Scale, (2) no imaging or laboratory test performed, and (3) discharge home. We used a binary multiple logistic regression model to identify factors associated with low-acuity visits. Results We analysed 778 PED visits (September 2019 to July 2020). Most children visiting our PEDs had a designated primary care provider (92%), with only 6% not having seen them during the last year. Fifty-five per cent of caregivers had asked for medical advice before coming to the PED. The proportion of low-acuity visits was 58%. Low-acuity visits were associated with caregiver's difficulties paying bills (aOR 2.6, 95% CI 1.6 – 4.4), having already visited a PED in the last 6 months (aOR 1.7, 95% CI 1.1 – 2.5) but not with parental education status, nor parental country of birth, parental employment status or absence of family network. Conclusion Economic precariousness is an important driver for low-acuity PED visits in Switzerland, a high-income country with compulsory health coverage where most children have a designated primary care provider and a regular pediatric follow-up. Primary care providers and PEDs should screen families for economic precariousness and offer anticipatory guidance and connect those in financial need to social support.